BCN–Co3O4 hybrid – a highly efficient catalyst for the oxygen evolution reaction and dye degradation. Issue 83 (22nd August 2016) - Balakrishnan, Thiruparasakthi; Anis, Mohamed; Arun, S.; Kumar, Mithin; Arun kumar, Sakthivel; Mayavan, Sundar
Abstract : The as-prepared Co3 O4 –BCN shows excellent activity towards the OER and dye degradation as compared to pristine Co3 O4 . Abstract : A simple one-step procedure for the preparation of nanosheets of crystalline 2D boron carbon nitride containing cobalt oxide (Co3 O4 –BCN) involving glycine–nitrate combustion chemistry is reported. The as-prepared hybrid is a highly active catalyst for dye degradation, and for the water oxidation reaction as compared to pristine Co3 O4 . Co3 O4 –BCN shows enhanced catalytic activity for the oxygen evolution reaction (OER) in alkaline electrolyte. The onset potential towards the OER is 0.406 V ( vs. Ag/AgCl) in 1 M KOH. A current density of 10 mA cm −2 has been achieved at an overpotential of 394 mV in 1 M KOH. The as-prepared hybrid exhibits highly-efficient degradation ability for methyl orange and methyl blue dyes under direct sunlight irradiation.